Pengaruh Strategi Pembelajaran Guided Inquiry Terhadap Keterampilan Metakognitif dan Berpikir Kritis Mahasiswa Pada Perkuliahan Pendidikan IPA SD - Anindita SHM Kusuma; Ahmad Busyairi (Journal of Classroom Action Research, 2023)
Students' metacognitive skills and critical thinking ability in Elementary Science Education lectures are still low, one of which is caused by conventional learning strategies that still dominate on lectures. The aim of this study was to determine the effect of the guided-inquiry learning strategy on the metacognitive skills and critical thinking ability of students in elementary science education courses. The research method uses quasi-experimental quantitative research, a nonequivalent control group design. The research population was PGSD Undergraduate Study Program students who were taking Elementary Science Education lectures. Based on the results of the study it can be concluded that there is an influence of guided-inquiry learning strategies on students' metacognitive skills and critical thinking ability. The corrected average for the metacognitive skills of the experimental class was 79.998, which was higher than the corrected average for the control class, which was 77.003. This shows that the metacognitive skills of students who are taught using the guided-inquiry strategy are higher than the metacognitive skills of students who are taught using conventional learning strategies. The average corrected critical thinking for the experimental class, which is 80.950, is higher than the corrected average for the control class, which is 78.105. This shows that the critical thinking ability of students who are taught using the guided-inquiry strategy are higher than the critical thinking ability of students who are taught using conventional learning strategies